A multi-institutional exploration of the social mobility potential of degree apprenticeships. Issue 4 (19th May 2021) - Smith, Sally; Taylor-Smith, Ella; Fabian, Khristin; Zarb, Mark; Paterson, James; Barr, Matthew; Berg, Tessa
ABSTRACT: This mixed-method study at six universities asked degree apprentices about their trajectories into the apprenticeship, to better understand the social mobility potential of apprenticeships. The degree apprenticeship offers a route to a degree for apprentices, who are employees studying for a degree. As a new model, little is known about the apprentices: who they are, their journey towards this degree, and whether they fulfil the social mobility aspirations expressed by apprenticeship policymakers. Computing and IT apprentices at six universities in Scotland, UK, were surveyed (n = 160) to ask about their background and previous experience. Interviews (n = 28) were carried out with apprentices studying with one of the institutions, to enquire how their backgrounds impacted on their journey to this point. By taking a multi-institutional approach, the study reports findings across different degree apprenticeships and geographical locations. Apprentices were found to be drawn from all socio-economic groups and represented those new to work and upskillers, already in work. For upskillers, the degree apprenticeship offered a belated opportunity for degree-level study. However, young people recruited into the apprenticeship were disproportionally from more privileged groups. We make recommendations for recruitment and selection processes to increase equality of access to degree apprenticeship places.